Application of Generic Porter Strategy for UMKM in Facing MEA - Julita Julita; Hasrudy Tanjung (Proceedings of AICS - Social Sciences, 2017)
In welcoming the ASEAN Economic Community (MEA), we will enter a new phase with our neighboring countries, especially Asean members. One of the main pillars of the MEA is the free flow of goods, ie in 2015 the trade of goods in the Asean region is carried out freely without any obstacles, whether tariff or non-tariff. MEA applies the Common Effective Preferential Tariff (CEPT) scheme previously applied at the Asean Free Trade Area (AFTA), ie a gradual decrease in tariffs for certain types of goods carried out within the agreed timeframe. This study aims to find the problems that often inhibit the development of SMEs in Deli Serdang District in competitive advantage, especially in the face of MEA, for it needed a strategy in creating competitive advantage in the era of MEA. There are many strategies for creating competitive advantage and one of Porter's generic strategies. This strategy provides success in the company so that researchers want to adopt generic strategy Porter for UMKM especially in Deli Serdang Regency. This research is planned for 3 years, and based on 1st year research result, it is very necessary for cooperation and role of Government and related institution in increasing competitive advantage and readiness of UMKM perpetrator in facing Asean Economic Community (MEA), while strategy used to face MEA Are: a) five forces porter b) innovation and technological capabilities of UMKM actors and government attention, next 2) compilation of generic Porter strategy development model, development of Generic Porter Strategy model and Generic Porter Strategy Model Design and report Research, Year 3) stage of socialization and implementation and book making.